Ionic liquid based Fluoropolymer solid electrolytes for Lithium-ion batteries - Serra, J. P. (2020)
Composite materials based on ionic liquids (ILs) / poly(vinylidene fluoride) (PVDF) and their copolymers have emerged as an interesting approach to develop high ionic conductivity solid polymer electrolytes (SPEs) for lithium-ion battery application. This work reports the development of SPEs based on fluoropolymers, PVDF and poly(vinylidene fluoride co-hexafluoropropylene), PVDF-HFP, containing different ILs: 1-ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl) imide ([EMIM][TFSI]) and 1-butyl-3-methylimidazolium thiocyanate ([BMIM][SCN]). The influence of IL type and content on the morphological, wettability, physical-chemical, thermal, mechanical and electrochemical properties were evaluated. It is shown that, independently of the polymer matrix, both ILs improve surface wettability and increase the polar β phase content and crystallinity degree of the polymers. The mechanical properties show that the incorporation of IL in the composites results in a plasticizing behaviour. Further, the [BMIM][SCN]/PVDF-HFP with 40 wt.% IL content shows the best room temperature ionic conductivity of 0.15 mS.cm-1 with excellent electrochemical stability in the 0.0 - 5.0 V potential window. The initial discharge capacity value at C/8-rate is 148 mAh.g-1 and 124 mAh.g-1 for the [BMIM][SCN]/PVDF and [BMIM][SCN]/PVDF-HFP composites, respectively, with high coulombic efficiency (98%). At C/8-rate, batteries with [BMIM][SCN]/PVDF-HFP show the lowest capacity fade (16 % after 50 cycles) of the prepared composites. Thus, it is demonstrated the suitability of developing SPEs based on IL and fluorinated polymers for the next generation of solid-state room temperature lithium-ion batteries.